Socio-Cultural Influences of Reproductive Technologies and Family Concepts in Contemporary Society - Galić, Branka, sociolog (Array, 2014)
On one hand, technology has enormously increased the possibility for planning and controlling the reproductive life. On the other hand, control of reproductive technologies (RT) by the governments, corporative interests, medical professionals, religious institutions and other political actors, has certainly influenced the restrictions of female autonomy in establishing reproductive selfdetermination. Access to and attitude towards reproductive methods and techniques have significantly influenced and are still influencing the direction of many women’s lives. Likewise, the reproductive technologies profoundly influence cultural ideas about femininity, motherhood and family. Women have experiences of various types of control over their reproductive abilities, depending on their socio-economic and cultural circumstances. RT expand choices but the development of new technologies shapes and is being shaped by different social interests regarding both reproduction and cultural context. Reproduction remains an engendered phenomenon in the 21st century, but it also challenges the approach to reproduction beyond normative heterosexual family and traditional ideas about reproduction. At the same time it expands our public imagination on what constitutes a family. Since RT provide a possibility for reproduction outside the traditional nucleus family, discussion on family transformation in contemporary society opens a new array of complex relations knjizica sazetaka.indd 39 15.11.2013 14:26:22 40 Mlade žene i rodna ravnopravnost u postjugoslavenskim društvima: Istraživanja, prakse i politike of post-modernity in which some women and couples accomplish their individual choices in their individual reproductive arrangements. An intimate relationship between femininity and construction of motherhood make RT an important place for exploring the meanings of body, biology and politics. Although political and cultural norms regarding the usage of contraception, abortion and infanticide vary historically and geographically, women have always sought their own selfdetermination about pregnancy and family size. Nowadays, the dynamics of changes in the structure of nucleus family and the possibilities of usage of RT have conditioned variant choices of family in the post-modern era.